2018
DOI: 10.1021/acs.organomet.7b00889
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrogenation of Dimethylamine–Borane Catalyzed by Half-Sandwich Ir and Rh Complexes: Mechanism and the Role of Cp* Noninnocence

Abstract: Half-sandwich Cp*RhIII complexes (Cp* = η5-1,2,3,4,5-pentamethylcyclopentadienyl) supported by 2,2′-bipyridine or 4,4′-di-tert-butyl-2,2′-bipyridine catalyze dehydrogenation of dimethylamine–borane (Me2NH·BH3) to produce H2 and dimethylamino–borane dimer (Me2NBH2)2 with turnovers of 2200. The IrIII analogues, on the other hand, display dramatically poorer catalytic activity. Mechanistic inferences drawn from stoichiometric reactions and DFT calculations suggest noninnocent involvement of the Cp* moiety as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…32 Added [H 2 B(NMeH 2 ) 2 ][BAr F 4 ] (10 equiv) significantly slows catalysis, now taking 24 h for completion to produce very short polymer ( M n = 2 800 g/mol, Đ = 2.3). This argues against its role in productive catalysis, in contrast with other systems, 10,29,46 in particular the [Rh(Xantphos- i Pr)] + system, where it promotes catalysis. 10 At low relative concentrations, H 3 B·THF presumably acts to titrate out NMeH 2 , while we propose that excess [H 2 B(NMeH 2 ) 2 ] + acts to poison catalysis, possibly sequestering NMeH 2 via N–H···NMeH 2 hydrogen bonding, as noted for related bis(phosphine)boronium salts.…”
Section: Results and Discussionmentioning
confidence: 97%
“…32 Added [H 2 B(NMeH 2 ) 2 ][BAr F 4 ] (10 equiv) significantly slows catalysis, now taking 24 h for completion to produce very short polymer ( M n = 2 800 g/mol, Đ = 2.3). This argues against its role in productive catalysis, in contrast with other systems, 10,29,46 in particular the [Rh(Xantphos- i Pr)] + system, where it promotes catalysis. 10 At low relative concentrations, H 3 B·THF presumably acts to titrate out NMeH 2 , while we propose that excess [H 2 B(NMeH 2 ) 2 ] + acts to poison catalysis, possibly sequestering NMeH 2 via N–H···NMeH 2 hydrogen bonding, as noted for related bis(phosphine)boronium salts.…”
Section: Results and Discussionmentioning
confidence: 97%
“…We have recently 28,31 The role of boronium in productive turnover has also been probed in pincer-like [Rh(Xantphos-i Pr)] + systems, B, 30 and Pt-based systems related to E, 28 Scheme 2, as well as others. 29 We propose a similar set of fundamental processes operates here, in which amine-induced B-H bond cleavage gives a metal hydride that is then reprotonated. Two realistic scenarios presented themselves for this process: (a) the boronium route as described, or, (b) one that invoked the formation of ammonium (Scheme 6 Fig.…”
Section: The Role Of Boronium [Nme 2 H 2 ][Bar F 4 ] Nme 2 H and Thmentioning
confidence: 96%
“…Depending on the catalyst system a number of different routes have been proposed to operate for this, that all invoke σ-amine-borane complexes 18,19 as early intermediates (Scheme 2): (i) step-wise, or concerted, inner sphere; 17,[20][21][22] (ii) ligand-assisted cooperation; [23][24][25][26] and (iii) hydride transfer to form a boronium 27 cation that reprotonates the transiently formed hydride. [28][29][30][31] The initial reports of dehydropolymerisation of H 3 B•NMeH 2 used the neutral pincer catalyst Ir(POCOP)H 2 7,8,16 [A, POCOP = κ 3 -C 6 H 3 -2,6-(OP t Bu 2 ) 2 ], Scheme 3. A number of closely related pincer-based systems have since been used to catalyse amine-borane dehydrocoupling.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found that [Cp*Rh] complexes bearing bidentate diphosphine [ 25 ] or hybrid phosphine-quinoline ligands [ 26 ] are not capable of similar catalysis. Thus, although the role of supporting bidentate ligand structure in formation of [Cp*H] intermediates is not yet clear, it is of high interest considering the new reactivity manifolds that may be accessible with [Cp*H] complexes [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%